Technical Advance: Measurement of iNKT cell responses at the single‐cell level against rare HIV‐1‐infected dendritic cells in a mixed culture. Issue 3 (21st December 2012) - Andersson, Sofia K.; Paquin‐Proulx, Dominic; Kroll, Mirko; Sandberg, Johan K.; Moll, Markus
Abstract : A microscopy‐based assay to measure iNKT cell responses against rare HIV‐1 infected dendritic cells, infected with an eGFP expressing reporter virus. Abstract : iNKT cells recognize lipid antigens, such as α‐GalCer, presented in complex with CD1d expressed by DCs. Exposure of DCs to HIV‐1 can lead to productive infection, and it was demonstrated recently that HIV‐1 inhibits CD1d surface expression in an apparent mode of immune evasion. However, studies of the interaction between T cells, including iNKT cells and HIV‐infected DCs in vitro, are hampered by the low frequency of productive infection in DCs. Here, we demonstrate the utility of full‐length HIV‐1 modified to express eGFP to address this problem. This virus allowed identification of single, rare productively infected cells in a mixed DC population by fluorescence microscopy and enabled detailed studies of the interaction of such cells with individual iNKT cells. iNKT cell responses to α‐GalCer presented by HIV‐1‐positive and ‐negative DCs were quantified by intracellular IFN‐γ staining in iNKT cells forming conjugates with DCs. Whereas complex formation was observed between iNKT cells and uninfected and infected DCs, only iNKT cells in contact with uninfected DCs produced IFN‐γ. This microscopy assay, based on full‐length HIV‐1 modified to express eGFP, thus allows detailed evaluation of HIV‐1 immune‐evasion mechanisms in rare virus‐infected live DCs.